Gel Formulation for Hand Sanitizer from Ethanol Extract of Mulberry Leaf (Morus Alba L.) - Sutaryono Sutaryono; Hendra Budiman; Anita Agustina Styawan; Nurul Hidayati; Dayah Ainus (Urecol Journal. Part D: Applied Sciences, 2021)
During the Covid 19 pandemic, a handsanitizer product has emerged which functions as a hand washing disinfectant for the prevention of the Covid 19 virus. One of the ingredients that can be made handsanitizer gel is the mulberry plant (Morus alba L.) because it contains many flavonoids which act as antiseptics against bacteria. The research objective was to determine the handsanitizer gel formulation with the concentration of carbopol and propylenglycol which can produce good physical properties. The research design used an experiment, with the mulberry leaf preparation material macerated using 70% ethanol. Mulberry leaf ethanol extract (Morus alba L.) as the active substance and made 3 formulas with variations in the concentration of carbopol: propylenglycol formula I (0.5%: 15%), formula II (1.25%: 12.5%), formula III (2%: 10%). The three formulas were tested for physical properties and analyzed by ANOVA with a confidence level of 95%. The results showed that the handsanitizer gel formulation with carbopol increased viscosity and stickiness, while propylenglycol increased the dispersibility. The 1.25% formula: 12.5% ??produces the best physical properties, with a pH test of 6, a viscosity test of 150 dPas, a spreadability test of 6.5 cm, a sticky power test of 2.39 seconds and a protective power test without red stains.